Іван Кожедуб – найрезультативніший льотчик-винищувач антигітлерівської коаліції (до 100-річчя з дня народження) - Лисенко, О.; Филь, О. (Український історичний журнал, 2020)
Мета цієї розвідки полягає у спробі реконструкції історичного портрета одного з найяскравіших учасників Другої світової війни. Методологія дослідження ґрунтується на засадах історизму, використанні прийомів історичної біографістики та військово-історичної науки. Наукова новизна визначається залученням маловідомих архівних джерел, статистичних викладів із зарубіжних видань, що дало змогу не тільки відтворити цікаві деталі біографії знаного льотчика, а й визначити місце цієї постаті у шерегу кращих пілотів Другої світової війни. Висновки. Особистість І.Кожедуба формувалася під впливом тогочасних реалій: партійної диктатури, ідеологічної індоктринації суспільства, а також важких соціально-побутових умов. Ці обставини визначили його світогляд і загартували характер, спонукаючи до самовдосконалення й навчання, розвиваючи вміння самостійно ухвалювати рішення та нести відповідальність за їх наслідки, а ще здатність цінувати людей, з якими він поділяв усі випробування воєнної доби. На підставі статистичних даних, проаналізованих вітчизняними та зарубіжними фахівцями, можна впевнено стверджувати, що І.Кожедуб став найрезультативнішим пілотом у збройних силах держав антигітлерівської коаліції. Констатується, що бойові заслуги цієї людини знаходять належне відображення у мнемонічних практиках. The purpose of this reconnaissance is an attempt to reconstruct a historical portrait of one of the brightest participants of the World War II – Ivan Kozhedub. The research methodology based on the principles of historicism, the use of techniques of historical biography and military history, as well as the modern conceptual apparatus with which they operate. The novelty of the text determined by the involvement of little-known archival sources, statistical statements from foreign publications, which allowed not only to reproduce interesting details of the biography of the famous pilot, but also to determine the place of this figure among the best pilots of World War II. The refusal to glorify and idealize the main character made it possible to actualize other contexts related to his life trajectories and military affairs. Conclusions. I.Kozhedub personality formed under the influence of the realities of the time: party dictatorship, ideological indoctrination of society – on the one hand, and difficult social and living conditions – on the other. These circumstances defined his worldview and hardened his character, encouraging self-improvement and learning, developing the ability to make decisions independently and be responsible for their consequences, as well as the ability to appreciate people with whom he shared all the trials of wartime. Based on statistical data analyzed by domestic and foreign experts, it is safe to say that I.Kozhedub became the most effective pilot in the armed forces of the Anti-Hitler coalition. It stated that the military merits of this man and warrior properly reflected in mnemonic practices.